Solid Waste Landfill Site Selection; Konya City Sample - Büşra Altay; Zekeriya Can Erbil (Turkish Journal of Agriculture: Food Science and Technology)
In developing countries, consumption habits have changed with the increase in population, the development of technology and industrialization. For this reason, good management of the increase in the amount of solid waste by municipalities is very important for the health and sustainability of nature. The location of the facility to be established is important for the regular storage and efficient disposal of solid wastes. Site selection of landfill facilities in the ‘Site Management and Operation Guide for Landfill Facilities’ published by the General Directorate of Environmental Management; The ratio of the volume to the area, the distance to the buildings, the wind direction, the external view (landscape), the effect on the traffic on the side, the profit from the finished facility, and the effect on the water are evaluated under the sub-headings. With the ‘Konya Solid Waste Management Project’, ‘Aslım Sanitary Landfill’, which was used until 2017, was closed. Instead, the ‘Konya Solid Waste Landfill Site’, which was established in a different region to meet the need, was put into operation. In the study to be carried out in this context; Both fields were evaluated according to the specified criteria and compared with each other using the Analytical Hierarchy Method. As a result, it is aimed that the success rate of the location selection of the new solid waste storage area will be revealed and it will be a base for similar studies to be done in the future.